2002
DOI: 10.1093/oxfordjournals.molbev.a004079
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Gene Duplication in the Genomes of Drosophila, Nematode, and Yeast

Abstract: We conducted a detailed analysis of duplicate genes in three complete genomes: yeast, Drosophila, and Caenorhabditis elegans. For two proteins belonging to the same family we used the criteria: (1) their similarity is > or =I (I = 30% if L > or = 150 a.a. and I = 0.01n + 4.8L(-0.32(1 + exp(-L/1000))) if L < 150 a.a., where n = 6 and L is the length of the alignable region), and (2) the length of the alignable region between the two sequences is > or = 80% of the longer protein. We found it very important to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
308
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(316 citation statements)
references
References 27 publications
6
308
0
2
Order By: Relevance
“…The average rate of origin of new duplicates in this study, 0.01/gene/MY, is about the same as that reported in our earlier study. Gu et al (2002) also recently reported estimates of the rate of origin of duplicates genes in D. melanogaster, C. elegans, and S. cerevisiae. As in our study, these authors employed pre-screening devices to avoid pseudogenes, alternatively spliced variants, and annotation errors, but their additional methods of analysis deviated from those used herein in a number of ways.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The average rate of origin of new duplicates in this study, 0.01/gene/MY, is about the same as that reported in our earlier study. Gu et al (2002) also recently reported estimates of the rate of origin of duplicates genes in D. melanogaster, C. elegans, and S. cerevisiae. As in our study, these authors employed pre-screening devices to avoid pseudogenes, alternatively spliced variants, and annotation errors, but their additional methods of analysis deviated from those used herein in a number of ways.…”
Section: Discussionmentioning
confidence: 98%
“…As in our study, these authors employed pre-screening devices to avoid pseudogenes, alternatively spliced variants, and annotation errors, but their additional methods of analysis deviated from those used herein in a number of ways. For example, Gu et al (2002) did not make a distinction between the number of duplicate pairs and the actual (necessarily smaller) number of duplication events; they included very large multigene families, whereas we used an arbitrary cutoff for family size of five; they attempted to remove incomplete or chimeric duplicates; and they eliminated some duplicate pairs in which the nucleotide substitution levels in flanking regions exceeded those in silent sites. Despite these differences, it is comforting that estimates from both studies for B appear to deviate by no more than a factor of three.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can tolerate more nucleotide changes than their single copy counterparts. The phenomenon is evident most clearly on a whole-genome scale 15,16 , where recent gene duplicates in various eukaryotes tolerate 10-fold more amino acid changes than old duplicates 15 . Eventually, the accumulating changes may cause duplicates to diversify their function, and sometimes quite rapidly 11,17,18 .…”
Section: Gene Duplications Cause Robustnessmentioning
confidence: 99%
“…Duplicated genes within the Arabidopsis genome were identified following a method introduced by Gu and coworkers [54,55]. This method is based on an all-againstall sequence comparison of protein sequences that are not splice variants of the same gene and require at least 30% amino acid sequence identity with adjusted higher thresholds for short sequences.…”
Section: Characteristic Sequence Signatures In Longer Upstream Regionmentioning
confidence: 99%